The Moderating Role of Religiosity on Green Finance, Trust, and Interest in Green Financial Products - Ummi Kalsum; Mister Candera; Randy Hidayat; Novia Zahrah; Belliwati Kosim (School of Business, Bogor Agricultural University (SB-IPB), 2026)
Background: The increasing urgency of environmental issues has encouraged the expansion of sustainable financial practices, including the development of green finance. Despite this progress, public familiarity with green financial products and confidence in related institutions remain relatively limited. In the Indonesian context, especially among religious-based educators such as Muhammadiyah teachers, financial decisions may also be influenced by spiritual and ethical considerations. Therefore, this study investigates the roles of green finance literacy and institutional trust in shaping interest in green financial products, with religiosity examined as a moderating variablePurpose: This research aims to evaluate the influence of green finance literacy and trust on teachers’ intention to use green financial products and to assess whether religiosity strengthens these relationships.Design/methodology/approach: A quantitative survey design was applied in this study. Respondents were selected using proportionate stratified random sampling from Muhammadiyah senior high school and vocational school teachers in Palembang. Data were collected through structured questionnaires with a five-point Likert scale and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM).Findings/Results: The findings demonstrate that green finance literacy and trust significantly affect interest in green financial products. Religiosity does not strengthen the relationship between literacy and intention, but it significantly reinforces the effect of trust on intention.Conclusion: The adoption of green financial products among Muhammadiyah teachers is primarily influenced by knowledge and institutional trust. Religiosity contributes indirectly by amplifying the role of trust rather than literacy.Originality/value (State of the art): This study contributes to sustainable finance literature by integrating religiosity into the green finance behavioral model and focusing on religious educators as a specific social group in Indonesia Keywords: green finance literacy, trust, interest in green financial products, religiosity, SEM